The changing role of emerging and frontier markets in global portfolio diversification - Eero Pätäri; Sheraz Ahmed; Elena John; Ville Karell (Cogent Economics & Finance, 2019)
Although the literature on the benefits of diversifying equity portfolios to emerging markets is abundant, the role of frontier markets in global equity portfolio diversification is clearly less examined. We contribute to the existing literature by examining three different, though closely related, spillover effects (i.e., return, shock and volatility spillovers) between developed, emerging and frontier markets over the period from June 2002 to December 2016. We also investigate the time-variability in the cross-market correlations within the same period. Moreover, we divide the full-sample period into two sub-periods to find out how the intensity of integration of emerging and frontier markets with three developed equity markets (represented by the US, European and Japanese stock markets) has changed or varied during the sample period. Based on both correlation analysis and the VAR(1)–BEKK-GARCH(1,1) model, the global financial crisis and the Euro-zone crisis 2009–2012 have changed the interlinkages between developed and developing markets, as well as those between emerging and frontier markets. The results show that after the global financial crisis, particularly frontier markets have become more integrated with the developed markets, whereas in case of emerging markets, the same tendency has taken place already before the financial crisis. The increased cross-market integration has important practical implications for risk management of global equity portfolios.